Long-term symptomatic control of Zenker diverticulum by flexible endoscopic mucomyotomy with the hook knife and predisposing factors for clinical recurrence. (2nd June 2016) - Brueckner, Juliane; Schneider, Annette; Messmann, Helmut; Gölder, Stefan Karl
ABSTRACT: Objective Flexible endoscopic treatment for Zenker diverticulum (ZD) is well established. Although recurrence of symptoms is relatively frequent, it has hardly been studied. In the present study, we analyse the long-term development of ZD patients' symptoms after successful endoscopic mucomyotomy, as well as interventional safety, sustainability of success, and predisposing factors for clinical recurrence.Methods Forty-six consecutive patients (54% male, mean age 67 years) with symptomatic ZD were treated using a hook knife and soft diverticuloscope. Follow-up interviews at 1 and 6 months inquired about a broad pool of symptoms and the dysphagia score. For further analysis, patients were retrospectively stratified into a 'recurrence' and 'no recurrence' group.Results After 100% initial success, 30% of patients reported recurrence of symptoms after 4.4 months (range 1-40) and were re-treated (mean 1.39 sessions/patient). Though the 'recurrence' group showed a higher dysphagia score and frequency past intervention, endoscopic re-treatment achieved equally good results as in the 'no recurrence' group. Before treatment, 'recurrence' patients had more severe symptoms, such as vomiting (frequency score 2.13 vs. 0.92; p < 0.05), ZD-related insomnia (1.65 vs. 1.08, n.s.), and a higher dysphagia score (2.25 vs. 1.59, n.s.). Also, the 'recurrence' group had larger diverticula, more men, slightly younger age and a longer duration of symptoms.Conclusions Endoscopic treatment of ZD with hook knife and soft diverticuloscope is safe and effective. Despite considerable clinical recurrence, re-treatment achieved a long-lasting freedom of symptoms. Male patients with a high dysphagia score and severe symptoms were more likely to experience recurrence.